2019
DOI: 10.1111/bjd.18227
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable risk factors and the development of psoriatic arthritis in people with psoriasis

Abstract: Summary Background Psoriatic arthritis (PsA) is a progressive and often destructive joint disease affecting approximately 20% of people with psoriasis. Objectives To investigate associations between obesity, changes in body mass index (BMI), alcohol intake and smoking status and the development of PsA in people with psoriasis. Methods We undertook a cohort study involving incident cases of psoriasis identified from the U.K. Clinical Practice Research Datalink between 1998 and 2014. The associations between smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 33 publications
1
51
0
3
Order By: Relevance
“…In fact, among patients with psoriasis, a reduction in BMI may reduce the risk of PsA. A large PsA cohort study found that reducing BMI over a 10-year period was associated with a reduction in the risk of developing PsA compared with BMI remaining constant over the same period [ 55 ]. Patients with PsA are at a higher risk for cardiovascular disease including myocardial infarction and major adverse cardiovascular events (MACE) after accounting for traditional cardiovascular risk factors [ 3 , 56 , 57 ].…”
Section: Management Of Obesity As a Cardiovascular Risk Factor In Psamentioning
confidence: 99%
“…In fact, among patients with psoriasis, a reduction in BMI may reduce the risk of PsA. A large PsA cohort study found that reducing BMI over a 10-year period was associated with a reduction in the risk of developing PsA compared with BMI remaining constant over the same period [ 55 ]. Patients with PsA are at a higher risk for cardiovascular disease including myocardial infarction and major adverse cardiovascular events (MACE) after accounting for traditional cardiovascular risk factors [ 3 , 56 , 57 ].…”
Section: Management Of Obesity As a Cardiovascular Risk Factor In Psamentioning
confidence: 99%
“…Obesity, diabetes, hypertension, hyperlipidemia and the metabolic syndrome (MetS) are overrepresented in both psoriasis and PsA [2][3][4] and the patients are at increased risk of cardiovascular morbidity [5][6][7][8][9]. Studies indicate that obesity may play a pathophysiologic role in psoriasis and PsA, since obesity is associated with an increased risk of developing these conditions [10][11][12][13]. Obesity is also associated with increased disease activity [14,15] and poorer effect of treatment [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…body mass index) changes the outcome, this study provides further supporting obesity as a causal risk factor for PsA. 3 Now comes the hard work: putting this knowledge into action. This new evidence supports two important future needs: (i) the need for mechanisms to help our patients to lose weight and (ii) the need for PsA prevention trials in psoriasis.…”
mentioning
confidence: 57%
“…In demonstrating that changing the level of the risk factor (i.e. body mass index) changes the outcome, this study provides further supporting obesity as a causal risk factor for PsA . Now comes the hard work: putting this knowledge into action.…”
mentioning
confidence: 61%